Linear Solvation Energy Relationship of Some Aromatic Compounds in RP-HPLC - Jin, Y.; Yan, L.H.; Jin, M.J.; Cheng, Y.D.; Row, K.H. (Asian Journal of Chemistry, 2013)
The fundamental chemical interactions governing the retention of 5 aromatic compounds such as benzene, toluene, chlorobenzene, o-xylene and 1,2-dichlorobenzene were investigated in methanol/water mobile phase on a C18 column using linear solvation energy relationship (LSER) model. The ability of the linear solvation energy relationship to account for the chemical interactions underlying solute retention was shown. A comparison of predicted and experimental retention factors suggests that linear solvation energy relationship formalism is able to reproduce adequately the experimental retention factors of the solutes studied in the different experimental conditions investigated. The predicted retention factors by the linear solvation energy relationship model have good agreement with experimental data in the employed mobile phase conditions.